Factores endógenos y exógenos asociados a infección del sitio quirúrgico en adultos del departamento de cirugía, Hospital Iquitos, 2023 - Crispín Alvear, David Jonathan (2024)
INTRODUCTION: Surgical Site Infections (SSI) represent approximately 15-17% of infections acquired in a hospital setting, affecting 10-30% of abdominal surgeries and 30-35% of appendectomy complications, with the latter being the most frequent, constituting a significant public health issue. OBJECTIVE: To determine the endogenous and exogenous risk factors associated with surgical site infection in adult patients undergoing surgery in the Department of Surgery at Hospital Apoyo Iquitos, 2023. METHODOLOGY: This study is observational, cross-sectional, and retrospective of cases and controls. The study population consisted of 1712 adult patients who underwent surgical treatment in the Department of Surgery at Hospital Apoyo Iquitos during January to December 2023. Sample: 42 cases and 272 controls. Factors related to the patient and the surgical procedure were studied. Data were collected using a questionnaire and analyzed in Excel and SPSS v25. Odds Ratio (OR) was applied, and statistical significance was determined with 95% confidence intervals. RESULTS: The identified risk factors that were significantly associated (p-value < 0.05) with the presence of SSI were: Endogenous factors (Diabetes, Hypertension, ASA class III, and NNIS index 1 and 2) and exogenous factors (preoperative stay exceeding 24 hours, contaminated surgical wound, use of drains, and hospital stay longer than 7 days). CONCLUSIONS: The prevalence of SSI in this study is similar to what is expected for developing countries. The most notable risk factor in the multivariate analysis was a hospital stay longer than 7 days.